Negative Effects of Open Government: A Meta-Theory Analysis (Good Governance in Relation to Open Government Initiatives) - Andhika, Lesmana Rian (Jurnal Bina Praja, 2017)
Many studies merely focus on discussing the benefits of open government, but the negative effects of open government in a variety of published literary works are limited. The advantages of open government are for citizens to get easier access to data and government activity, regulation, and policies. A particular purpose of the research explores the conceptual theoretic from a variety of scientific literature and to understand the negative effects of open government. The method in this research article is a synthesis of qualitative research approach to meta-theory analysis. Data in the research is processed deductively from a variety of scientific literature. The results of the research study aim to explain open government, or open data is not necessarily to generate transparency in government activities. Participation and collaboration in some cases are still considered yet they significantly support open government. It is because a concept may not be appropriate in different places that were affected by the characteristics of the socio-cultural, economic, and democracy of a nation.